Kinetic vs. thermodynamic control of β-functionalized cyclic ketones: a theoretical investigation of regioselective formation of enolates. Issue 22 (29th September 2022) - Petroselli, Manuel; Bacchiocchi, Corrado
Abstract : The reported theoretical study sheds light on the regioselective formation of enolates in β-functionalized ketones, highlighting the importance of non-covalent interactions. Abstract : Thermodynamic- and kinetic-controlled deprotonation of symmetric and asymmetric ketones is a well-known process that leads to the formation of enolates, one of the most important intermediates in organic chemistry. To the best of our knowledge, no studies have been specifically reported on β-functionalized ketones in which regioselective formation of enolates could be less obvious and intuitive with respect to that observed in the most familiar α-functionalized analogues. Here we report a theoretical study on the effect of a set of kinetic parameters on the regioselctivity of β-functionalized cyclic ketones 1–6 . This study has shed light on some unexplained behaviours reported in the literature, highlighting the importance of non-covalent interactions in regiocontrolled processes.